Web Training by Using HTML and CSS to Attract Interest in Learning Programming for High School Students - Prya Artha Widjaja; Simon Prananta Barus; Ary Budi Warsito; Jose Ryu Leonesta; Sabrina Yose Amalia; Veronica Yose Ardilla; Nico Abel Laia (Jurnal Pengabdian Masyarakat Bestari, 2023)
In digital field, the need for programmers is increasing, but quality resources in the field of programming are still lacking. Many schools, in this case, high schools, have not taught programming in the school curriculum. This training is given to attract students' interest in learning programming. The chosen method is to teach how to make front-end views of web pages. This method was chosen because web programming is easier to learn and participants can see the results displayed live. From the activities that have been carried out, the participants were very enthusiastic about participating and asked for further training. It can be concluded that this training succeeded in attracting the interest of participants, namely high school students, to learn programming, specifically web programming.